I hope I join the band: narrative, affiliation, and antiracist rhetoric - Condon, Frankie, author; Utah State University Press, publisher (Colorado State University. Libraries, 2012)
Both from the Right and from the Left, we are stymied in talking well with one another about race and racism, by intransigent beliefs in our own goodness as well as by our conviction that such talk is useless. ... White antiracist epistemology needs to begin not with our beliefs, but with our individual and collective awakening to that which we do not know. Drawing on scholarship across disciplines ranging from writing and rhetoric studies to critical race theory to philosophy, I Hope I Join the Band examines the limits and the possibilities for performative engagement in antiracist activism. Focusing particularly on the challenges posed by raced-white identity to performativity, and moving between narrative and theoretical engagement, the book names and argues for critical shifts in the understandings and rhetorical practices that attend antiracist activism.
Keywords: Anti-racism; Rhetoric -- Social aspects; Racism; Racism in literature; Racism -- Study and teaching